Franz Kafka : Narration, Rhetoric, and Reading - Lothe, Jakob; Sandberg, Beatrice, 1942-; Speirs, Ronald (Book collections on Project MUSE., 2011)
"Franz Kafka: Narration, Rhetoric, and Reading presents essays by noted Kafka critics and by leading narratologists who explore Kafka's original and innovative uses of narrative throughout his career. Collectively, these essays by Stanley Corngold, Anniken Greve, Gerhard Kurz, Jakob Lothe, J. Hillis Miller, Gerhard Neumann, James Phelan, Beatrice Sandberg, Ronald Speirs, and Benno Wagner examine a number of provocative questions arising from Kafka's narratives and method of narration. The arguments of the essays relate both to the peculiarities of Kafka's story-telling and to general issues in narrative theory. They reflect, for example, the complexity of the issues surrounding the "somebody" doing the telling, the attitude of the narrator to what is told, the perceived purpose(s) of the telling, the implied or actual reader, the progression of events, and the progression of the telling. As the essays also demonstrate, Kafka's narratives still present a considerable challenge to, as well as a great resource for, narrative theory and analysis"--Publisher's description